Dynamics of Academic Mobility: Hegemonic Internationalisation or Fluid Globalisation. (2nd April 2015) - Scott, Peter
Abstract : Two broad frameworks are used to describe and analyse the mobility of academic staff. The first, and dominant, framework focuses on flows from the 'periphery' to the 'core', although that 'core' is also evolving (and is no longer dominated by North America and Western Europe but is increasingly likely to embrace dynamic East Asia systems). This first approach is labelled 'hegemonic internationalisation'. The second framework focuses instead on issues of development, the emergence of global communities and social movements. This is labelled 'fluid globalisation'. The article argues that the latter may be more useful for understanding trends in academic mobility.